Pengaruh Penggunaan Limbah Tempurung Kelapa pada Beton Mutu Rendah - Fiqri, Khairul; Suhendra, Suhendra; Dony, Wari (Jurnal Civronlit Unbari, 2025)
Coconut shell waste is one or other abundant organic wastes found in the Jambi region; however, its utilization in the construction sector remains very limitedThe use of coconut shells as a partial substitute for gravel in low-strength concrete offers an environmentally friendly alternative aligned with sustainable development principles. Therefore, this study was conducted to examine the effect of adding coconut shell material on the compressive strength of low-grade concrete and to assess its viability as a replacement for coarse aggregate. The study also aimed to determine whether the resulting concrete meets the compressive strength standards outlined in the Indonesian National Standard (SNI) for low-strength concrete. A quantitative experimental method was employed, with coconut shells incorporated into the concrete mix at 2.5%, 5%, and 7.5% of the total coarse aggregate. Cylindrical test specimens measuring 15 cm in diameter and 30 cm in height were prepared. Compressive strength tests were conducted at 7, 14, and 28 days following the procedures in SNI 7656:2012, and the data were analyzed descriptively using quantitative methods. The results showed that higher proportions of coconut shell substitution corresponded to a gradual decrease in compressive strength. The control concrete at 28 days reached 24.24 MPa, while the mixture containing 7.5% coconut shell achieved 17.02 MPa. Although a reduction in strength was observed, all mixtures still met the minimum design requirement of 15 MPa. In conclusion, the addition of coconut shells leads to a gradual decline in compressive strength, but the concrete remains within the acceptable range for low-strength applications.Concrete containing coconut shells can still be utilized for non-structural applications, provided that quality control is properly maintained. Hence, the use of coconut shell as a partial replacement for coarse aggregate holds potential for limited application in environmentally sustainable construction.